Роль библиотечных вузов в планировании научно-исследовательской работы в области библиотековедения - Владимиров, Лев (Knygotyra, 1976)
The paper is dealing with the system of planning of scientific research in the field of library science as functioning in the Soviet library schools. The system has its characteristic features: first of all, the targets of the plan are to be brought into conformity with the acute needs of the society, there also must be taken into consideration the existing material conditions necessary to carry out the research plan, and finally, the research planned or the results achieved by other research institutions in the respective fields, and that not only in the Soviet Union, but also abroad. The research plans worked out in the library schools for one-year and five-year periods have to be founded upon these general and fundamental trends and targets of the development of research, as they are defined in the long-term (fifteen-year) plans. The process of working out the research plans begins within the respective departments of the school. The plans have to reflect the versatile research activities of the department, not only the individual research works carried out by each member of the faculty, but also the works carried out through a postgraduate thesis or done on the basis of a contract with other institutions, and even the research activities of the students’ research societies. But the departments, in spite of this diversity of the research activities, have to avoid a waste of research efforts and to swing all these efforts towards the solution of actual complex problems. Great importance for a rational planning of research has the establishment in the USSR of a centralized state system of registration and control of research works. An important step towards the creation of an analogical world system is the establishment by UNESCO of the ISORID.